1970
DOI: 10.1161/01.res.27.6.1047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hematocrit and Inertial Losses on Pressure-Flow Relations in the Isolated Hindpaw of the Dog

Abstract: The effect of hematocrit on pressure-flow relations was studied in the perfused isolated hindpaw of the dog. Blood and suspensions of erythrocytes (RBC) in albumin-Ringer solution, hematocrit range of 0 to 80%, were used as perfusates. Flow resistance was found to increase markedly with hematocrit. No significant difference was found between pressure-flow data obtained with blood and RBC in albumin-Ringer solution when comparisons were made at comparable hematocrits, indicating negligible effect of RBC aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Roos calculated that pulmonary perfusion pressure increases three-fold when the blood hematocrit is raised from 40%to 80% (5). Benis and associates found that pulmonary resistance increases three-fold when the hematocrit is increased from 42%to 80%in perfused canine hindpaws (6). Thus in the present case, the increase in hematocrit is likely related in part to systemic hypertension and pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…Roos calculated that pulmonary perfusion pressure increases three-fold when the blood hematocrit is raised from 40%to 80% (5). Benis and associates found that pulmonary resistance increases three-fold when the hematocrit is increased from 42%to 80%in perfused canine hindpaws (6). Thus in the present case, the increase in hematocrit is likely related in part to systemic hypertension and pulmonary hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…These flow changes are not primarily caused by cerebrovascular con trol mechanisms, but rather by alterations in blood viscosity [13,14], Proper breathing, which involves both drive and timing, is achieved through a series of complicated feedback mechan isms. When there is disturbance in the function of this respiratory feedback sys tem, blood flow and more especially re gional CBF may contribute to delay in in formation transfer.…”
Section: Discussionmentioning
confidence: 99%
“…** 4 Within the past 2 years, however, there have been reports of elevations in pulmonary artery pressure and resistance at rest in some patients with established essential hypertension, in the absence of increases in pulmonary capillary wedge pressure or any evidence for left ventricular failure. 3 "' 358 The patients, however, did have left ventricular hypertrophy, so there remains the possibility that the increased pulmonary pressures and resistances represented residual effects of the elevated left heart filling pressures that probably occurred with activity in these patients. Similar studies in patients with mild uncomplicated or borderline hypertension would help to better assess effects of left ventricular dysfunction.…”
Section: Hypertensionmentioning
confidence: 99%
“…Most of these studies were made a number of years ago and reported normal pulmonary hemodynamics in hypertensive patients at rest, 3 "" 3 " with the exception of elevations accompanying left ventricular dysfunction. 1 " It was also known that with exercise, pressures and resistances in the pulmonary circuit in hypertensives became abnormally high, accompanied by abnormal elevations of pulmonary capillary wedge pressures.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation